Réponses

2014-10-07T11:11:50+02:00
9)
A = (1/2x - 3) (x + 2/3)
A = 1/2x² + 2/6x - 3x - 6/3
A = 3/6x² + 2/6x - 18/6x - 12/6
A = 3x² + 2x - 30

B = (3/5x - 1) (1/3x + 15)
B = 3/15x² + 45/5x - 1/3x - 15
B = 3/15x² + 135/15x - 5/15x - 225
B = 3x² + 130x - 225
 
Je te laisse continuer les deux autres

10)
A = 3 (x - 7) - 2 (x + 4)
A = 3x - 21 - 2x - 8
A = x - 29

B = x - 1 - 2x + 2 - 1
        4          3
B = 3x - 3 - 8x+ 8 - 12/12
        12         12
B = 3x - 3 - 8x + 8 - 12
B = - 5x - 7

Je te laisse faire les deux autres